Clinical efficacy of tacrolimus combined with glucocorticoids for idiopathic membranous nephropathy - LING Yi-sheng; HE Jian-ying; LIU Jun-lan; GUO Han-cheng (Linchuang shenzangbing zazhi)
Objective Although idiopathic membranous nephropathy（IMN） is a common cause of adult-onset nephrotic syndrome,its treatment remains controversial.Recent studies show tacrolimus is effective in the treatment of IMN.This study was performed to evaluate the efficacy and safety of tacrolimus（TAC） combined with glucocorticoids in patients with IMN.Methods Twenty patients with biopsy-proven IMN were collected in this retrospective study.TAC was given at 0.05-0.1 mg·kg-1·day-1 initially,in combination with oral administration of glucocorticoids(prednisone 0.5 mg·kg-1·day-1 or methylprednisolone 0.4 mg·kg-1·day-1).The primary outcome was the remission rate,whereas the secondary outcomes included the changes in serum albumin levels and daily urinary protein levels,and adverse events.Results After treatment with TAC combined with glucocorticoids for 3 months,the albumin levels had a significant improvement[（23.57 ± 4.51） g/L vs.（33.16 ±6.87） g/L,P<0.05],and the proteinuria had a significant decrease[（6.74 ± 3.08）g vs.（3.69 ±2.65） g,P<0.05].At the 6th month post-therapy,the albumin levels were significantly improved[（23.57 ± 4.51） g/L vs.（36.96 ± 6.63） g/L,P<0.05],and the proteinuria was significantly decreased[（6.74 ± 3.08） g vs.（2.48 ± 2.21） g,P<0.05].At the 12 th month post-therapy,the albumin levels were significantly improved[（23.57 ± 4.51） g/L vs.（37.30 ± 7.62） g/L,P<0.05],and the proteinuria was significantly decreased[（6.74 ± 3.08） g vs.（2.19 ± 2.10） g,P<0.05].At the end of the 18-month therapy,the albumin levels were significantly improved[（23.57 ± 4.51） g/L vs.（39.84 ± 4.31） g/L,P<0.05],and the proteinuria was significantly decreased[（6.74 ± 3.08） g vs.（1.26± 1.42） g,P<0.05].After treatment for 18 months,complete remission（CR） was achieved in 45%（9/20） of the patients and partial remission（PR） in 40%（8/20）,yielding a final response rate of 85%（17/20）.Two patients experienced relapses during the follow-up period of 12 month.There were no significant changes in creatinine,transaminase and glucose in blood.The patients had no serious adverse reactions during the treatment Conclusions In this study,treatment with tacrolimus showed a good efficacy with mild adverse reactions in patients with IMN.